Economic Evaluation and Biodiversity Conservation of Animal Genetic Resources - Jutta Roosen; Aziz Fadlaoui; Marco Bertaglia (Kiel University, Department of Food Economics and Consumption Studies, 2003)
Rapidly declining biodiversity has made international and national policies focus on the question of how best to protect genetic resources. Loss of biodiversity does not only concern wildlife, but equally affects agriculturally used species. These species, of foremost importance for the subsistence of humankind, are subject to pressures sometimes similar and sometimes very distinct from those of their wild counterparts. And so are the losses implied by this decline in diversity. This handbook was conceived within the project Sustainable conservation of animal genetic resources in marginal rural areas: Integrating molecular genetics, socio-economics and geostatistical approaches (ECONOGENE - EC-QLK5-CT-2001-02461) to review and design methods that can serve as a basis to guide conservation policies for livestock breeds at risk of extinction. It is part of the broader effort of a multidisciplinary research team assessing the diversity of European sheep and goat breeds. The final goal of the project is to assess the impact of current and future policies on these breeds.
Keywords: 330; Tier; Biodiversität; Kosten-Nutzen-Analyse; Willingness to pay; Tierschutz; Theorie; Welt